(untitled) (INNOVATIVE ECONOMY, 2025)
Bahlei R.R. INTERNATIONAL CORPORATIONS IN THE FORMATION OF GLOBAL MARKET CONJUNCTURE Purpose. The aim of the article is to identify key problems in the functioning of modern transnational corporations and to develop guidelines for improving their effectiveness in shaping a stable and balanced global market environment. Methodology of research. The achievement of the research objective is based on the application of a set of methods: system analysis (to study TNCs as open systems that shape market conditions); strategic management theory (to study the mechanisms of global influence of corporations on markets); scientific abstraction, induction, and deduction (to form hypotheses and analyse cause-and-effect relationships in the activities of TNCs); abstract and logical (for theoretical generalization of results and formulation of conclusions); graphic (for in-depth visual concretization of examples of market conditions formation by international corporations). Findings. The theoretical and organizational-practical foundations of the functioning of modern transnational corporations are considered. In the process of research, it was established that international corporations are key agents in shaping global market conditions thanks to their concentration of financial resources, innovative potential, and global production and distribution networks. It was found that TNCs determine the structure of international trade, the direction of investment flows, and the pace of technological change. It was proven that the active activities of corporations in the crisis conditions of the global economy intensify both integration and destabilizing processes. The main problems faced by international companies have been summarized: increased competition, geo-economic risks, regulatory restrictions, and the challenges of digitalization. Originality. The role of international corporations as key players in shaping the global market environment in the context of globalization and digitalization has been further clarified. Patterns of interconnection between the innovative activity of corporations and the dynamics of TNC development have been identified. Practical value. The obtained results are of applied importance for the formation of state policy in the field of regulating the activities of international corporations, developing strategies for attracting foreign investment, and ensuring the balanced integration of national economies into the global market. Key words: international corporations, TNCs, global markets, international market conditions, globalization, investments, international competition, market strategy, innovation.